PENERAPAN SISTEM HIDROPONIK BERBASIS LIMBAH RUMAH TANGGA SEBAGAI SOLUSI PERTANIAN BERKELANJUTAN DI DESA TRIREJO - Talita Nadia; Muhammad Resa Oktavianto; Dina Widianingrum; Rafi’ Ghatfhan Syafi’i; Doni Desta; Nur Baiti Jannati (Jurnal Pengabdian Masyarakat Sabangka, 2026)
Household waste issues, particularly food scraps and plastic bottles, remain environmental problems that have not been optimally addressed. Most of this waste is disposed of without further processing, thereby posing risks of pollution. On the other hand, limited yard space has led to low levels of sustainable household farming practices. This Community Service Program (KPM) aims to provide education as well as implement a simple hydroponic system by utilizing food waste as liquid organic fertilizer (POC) and plastic bottles as planting media. The approach applied is descriptive qualitative with community participation, covering stages of observation, training, hands-on practice, and evaluation. The results indicate an increase in community knowledge and awareness regarding household waste management, along with the ability to independently apply simple hydroponic techniques. The healthy condition of plants during the early vegetative phase serves as an indicator of program success. This activity contributes positively to environmental education and has the potential to be developed into a sustainable household-level solution.